Generalization of Loo Keng-Hua’s lemma for an algebraic number fields - Kalinka, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Калинка. Обобщение одной леммы Хуа Ло-Кена для алгебраических чиселV. Kalinka. Vienos Hua Lo-Keno lemos apibendrinimas algebrinių skaičių kūne